2023
DOI: 10.18280/ijsse.130116
|View full text |Cite
|
Sign up to set email alerts
|

The Safer City: A New Planning Perspective for the Traditional City Development

Abstract: The research deals with the concept of a safe city and the impact of security on cities, in an attempt to identify the most important physical characteristics and indicators necessary to achieve safety in cities. The research identified seven characteristics (access and movement, structure, control, ownership, protection, activity, management and maintenance). From these seven characteristics, eighteen indicators were derived that directly affected the achievement of safety in urban environments. These indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…More sustainable to create a more adaptive, responsive and robust approach, leading to a new concept called Green TOD. One of the early and strong proponents of green TOD is Cervero & Sullivan, describing it as an environmentally friendly version of TOD, where TOD can be combined with green urbanism (Alrobaee et al, 2023;Cervero & Sullivan, 2011).…”
Section: Urban Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…More sustainable to create a more adaptive, responsive and robust approach, leading to a new concept called Green TOD. One of the early and strong proponents of green TOD is Cervero & Sullivan, describing it as an environmentally friendly version of TOD, where TOD can be combined with green urbanism (Alrobaee et al, 2023;Cervero & Sullivan, 2011).…”
Section: Urban Sustainabilitymentioning
confidence: 99%
“…More sustainable to create a more adaptive, responsive and robust approach, leading to a new concept called Green TOD. One of the early and strong proponents of green TOD is Cervero & Sullivan, describing it as an environmentally friendly version of TOD, where TOD can be combined with green urbanism(Alrobaee et al, 2023;Cervero & Sullivan, 2011).Green TOD is a combination of urban and mobility concepts that prioritizes both pedestrian and cycling infrastructure and automated mobility, leading to significant environmental benefits. Energy self-sustaining systems and efficient building designs, in conjunction with resource management systems, aid in resource conservation, waste reduction, and emissions control, while also providing us with energy independence(Alaskary & Alrobaee, 2022;Niu et al, 2021).The city's environmental footprint is significantly reduced by leveraging the strategic placement of activities and uses near transportation hubs, along with facilities that facilitate a shift from car to public transportation and replacing trips with walking and cycling.…”
mentioning
confidence: 99%
“…Crime levels are one of the most important determinants of the quality of life and vitality of the place. sociologists consider that crime is linked to social and demographic factors such as income, level of education, and ethnic composition, while planners and architects associate them with design factors such as the nature of space, lighting, or directing entrances [15,16] and studies have confirmed that planning land uses, overlapping urban functions and building design are closely related to crime [17], Natural surveillance was one of the most important considerations limiting crime. The presence of people in space and the provision of different opportunities for them, whether walking, talking, sitting, or seeing, are considered "eyes on the street" and can follow events around them.…”
Section: Protection Against Crimementioning
confidence: 99%
“… Traffic network connectivity: Network connectivity is defined as the extent to which streets connect with a numerical density of intersections, a large number of short links, and a small number of culde-sacs [26]. It can be measured by dividing the number of real nodes by unit area, and a higher number indicates more intersections and high connectivity (Mecredy et al, 2011).…”
Section: Spatial Connectivitymentioning
confidence: 99%